Analisis Kesulitan Keterampilan Membaca Dalam mata pelajaran Bahasa Indonesia pada Siswa kelas II Sekolah Dasar - Siti Fatimah Azzahra; Gusti Yarmi; Karsih Karsih (Atletik Karya: Jurnal Pendidikan dan Olahraga Aktual, 2024)
Indonesian language instruction in elementary schools aims to improve students' oral and written communication. Indonesian serves as a primary tool for students to hone their language skills correctly and effectively. Reading skills in elementary school are divided into two phases: initial reading (lower grades) and further reading (upper grades). Initial reading skills influence students' readiness before entering the next learning stage. However, second-grade elementary school students often face difficulties in developing initial reading and writing skills. Factors such as socio-economic background, gender, and teaching methods used by teachers can affect the success of literacy programs. By considering these factors, we can improve students' literacy skills at the beginning level.